The Effect of Tympanic Membrane Perforation Site, Size and Middle Ear Volume on Hearing Loss - Mustafa Aslıer; Hüseyin Özay; Selhan Gürkan; Günay Kırkım; Enis Alpin Güneri (Turkish Archives of Otorhinolaryngology, 2019)

(untitled)
Objective:The aim of this study was to analyze the location and the size of perforation in cases with tympanic membrane perforation, its relation to the manubrium mallei and middle ear volume, and to investigate how these are correlated with the severity and frequencies of conductive hearing loss.Methods: This prospectively designed study included the patients who presented to the the Department of Otorhinolaryngology at the Dokuz Eylül University with hearing loss or tinnitus complaints in the period from June 2014 through June 2017 and were identified to have tympanic membrane perforation in their otoscopic examination. Patients who underwent myringoplasty and type 1 tympanoplasty and whose air-bone gap was found lower than 10 dB in the postoperative audiological examination were included in the study. Effects of the perforation size, the perforation site, and the relationship of the perforation with the manubrium, as well as the effects of the middle ear volume on the severity and frequency of conductive hearing loss were compared.Results: The study included 44 ears of 38 patients (13 male and 25 female) of whom six had tympanic membrane perforation in both ears. Air conduction threshold and air-bone gap were significantly found higher if the perforation area was wide (p<0.05), the perforation involved both the anterior and the posterior quadrants (p<0.05), had contact with the manubrium mallei (p<0.05), and the middle ear volume reduced (p<0.05).Conclusion: Solely tympanic membrane perforation affects hearing function; nevertheless, hearing function are better in cases, which have perforations small in size, no contact with manubrium mallei and well pneumatized middle ears.